Testing likelihood ratios produced from complex DNA profiles. (May 2015) - Taylor, Duncan; Buckleton, John; Evett, Ian
Abstract: The performance of any model used to analyse DNA profile evidence should be tested using simulation, large scale validation studies based on ground-truth cases, or alignment with trends predicted by theory. We investigate a number of diagnostics to assess the performance of the model using H d true tests. Of particular focus in this work is the proportion of comparisons to non-contributors that yield a likelihood ratio (LR) higher than or equal to the likelihood ratio of a known contributor (LRPOI ), designated as p, and the average LR for H d true tests. Theory predicts that p should always be less than or equal to 1/LRPOI and hence the observation of this in any particular case is of limited use. A better diagnostic is the average LR for H d true which should be near to 1. We test the performance of a continuous interpretation model on nine DNA profiles of varying quality and complexity and verify the theoretical expectations.